Methods and Means for Defense from Collateral Action of Vaccine Virus after Vaccination Against Smallpox - N. K. Chernikova; T. A. Bondareva; S. V. Borisevich; V. N. Podkujko; A. L. Khmelyev; T. V. Dorokhina (Антибиотики и Химиотерапия, 2020)
In connection with actuality of smallpox vaccination at present its methods and means are discussed to increase the safety of the first immunization with live vaccines.